Impaired renal function is associated with brain atrophy and poststroke cognitive decline. (24th May 2016) - Auriel, Eitan; Kliper, Efrat; Shenhar-Tsarfaty, Shani; Molad, Jeremy; Berliner, Shlomo; Shapira, Itzhak; Ben-Bashat, Dafna; Shopin, Ludmila; Tene, Oren; Rosenberg, Gary A.; Bornstein, Natan M.; Ben Assayag, Einor
Abstract : Objective: To evaluate the interrelationship among impaired renal function, brain pathology on imaging, and cognitive decline in a longitudinal poststroke cohort. Methods: The Tel Aviv Brain Acute Stroke Cohort study is a prospective cohort of mild-moderate ischemic stroke/TIA survivors without dementia who underwent a 3T MRI and were cognitively assessed at admission and for 24 months following stroke. Renal function was evaluated at admission by creatinine clearance (CCl) estimation. The volumes of ischemic lesions and preexisting white matter hyperintensities (WMH), brain atrophy, and microstructural changes of the normal-appearing white matter tissue were measured using previously validated methods. Results: Baseline data were available for 431 participants. Participants with a CCl <60 mL/min at baseline performed significantly worse in all cognitive tests over time ( p = 0.001) than those with a CCl ≥60 mL/min and had larger WMH volume and cortical atrophy and smaller hippocampal volume (all p < 0.001). After 2 years, 15.5% of the participants were diagnosed with cognitive impairment. Multiple logistic regression analysis, controlling for traditional risk factors, suggested CCl <60 mL/min at baseline as a significant predictor for the development of cognitive impairment 2 years after the index stroke (odds ratio 2.01 [95% confidence interval 1.03–3.92], p = 0.041). Conclusions: Impaired renal function is associated with increased WMH volume and cortical atrophy, known biomarkers of the aging brain, and is a predictor for cognitive decline 2 years after stroke/TIA. Decreased renal function may be associated with cerebral small vessel disease underlying poststroke cognitive decline, suggesting a new target for early intervention.